Brain circuitry associated with the development of substance use in bipolar disorder and preliminary evidence for sexual dimorphism in adolescents. Issue 1 (9th November 2016) - Lippard, Elizabeth T.C.; Mazure, Carolyn M.; Johnston, Jennifer A.Y.; Spencer, Linda; Weathers, Judah; Pittman, Brian; Wang, Fei; Blumberg, Hilary P.
ABSTRACT: Substance use disorders and mood disorders are highly comorbid and confer a high risk for adverse outcomes. However, data are limited on the neurodevelopmental basis of this comorbidity. Substance use initiation typically occurs during adolescence, and sex‐specific developmental mechanisms are implicated. In this preliminary study, we review the literature and investigate regional gray matter volume (GMV) associated with subsequent substance use problems in adolescents with bipolar disorder (BD) and explore these associations for females and males. Thirty adolescents with DSM‐IV–diagnosed BD and minimal alcohol/substance exposure completed baseline structural magnetic resonance imaging scans. At follow‐up (on average 6 years post baseline), subjects were administered the CRAFFT interview and categorized into those scoring at high ( ≥ 2: CRAFFTHIGH ) vs. low ( < 2: CRAFFTLOW ) risk for alcohol/substance problems. Lower GMV in prefrontal, insular, and temporopolar cortices were observed at baseline among adolescents with BD reporting subsequent alcohol and cannabis use compared to adolescents with BD who did not ( P  < 0.005, clusters ≥ 20 voxels). Lower dorsolateral prefrontal GMV was associated with future substance use in both females and males. In females, lower orbitofrontal and insula GMV was associated with future substance use, while in males, lower rostral prefrontal GMV was associated with future use. Lower orbitofrontal, insular, and temporopolar GMV was observed in those who transitioned to smoking tobacco. Findings indicate that GMV development is associated with risk for future substance use problems in adolescents with BD, with results implicating GMV development in regions subserving emotional regulation in females and regions subserving executive processes and attention in males. © 2016 Wiley Periodicals, Inc. Abstract : This study demonstrates regional gray matter volume decreases that may distinguish adolescents with bipolar disorder and elevated risk for future substance use problems. Preliminary findings suggest that in females, regions associated with internalizing behavior and affective processing are related to risk; in males, regions associated with attention and other executive processes are related to risk.